Brain calcifications: Fahr’s disease or syndrome - Dávila-Hernández, Carlos Alberto (2021)
A 58-year-old female patient was brought in for myclonies, tonic-clonic seizures, with a history of hypertension, diabetes mellitus, hypothyroidism, cerebral infarction sequelae. Clinical examination was found soporous, isochoric pupils, hyporeactive, right hemiparesis. The no-contrast brain tomographic studyshowed cerebral and cerebellar calcifications. It is discussed about the concepts of Fahr disease or syndrome.